Combined modality management of advanced cervical cancer including novel sensitizers. Issue 3 (7th March 2022) - Tseng, Michelle; Ngoi, Natalie YL; Tan, David SP; Tong, Pearl SY
Abstract : The management of advanced cervical cancer has evolved with time. Combined modality treatments for cervical cancer have been shown to improve clinical outcomes for these patients. The role of surgery is reviewed in this article for specific situations such as the treatment of bulky lymph nodes and even in the metastatic setting. External beam radiotherapy and brachytherapy techniques have improved which has decreased patient toxicity. Systemic therapy such as chemotherapy, immunotherapy, and novel sensitizing agents have been extensively studied and have shown promising results. The combination of these three different modalities of treatment can be tailored to each specific patient to achieve the best outcomes. We review the recent advances and various international guidelines for the management of cervical cancer in this article.